Нерв: стихи / Высоцкий Высоцкий - Высоцкий Владимир Семенович (Новинки "Современника", 1981)
Экземпляры: ф.2 (20210114) / Инвентарный номер: 59898 / Цена: 05.00 / Авт.знак: В93 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6-5